The meaning of separation from anonymity by Emmanuel Levinas - Saldukaitytė, Jolanta (Religija ir kultūra, 2013)
The present article discusses the notion of anonymous existence in the early writings of Emmanuel Levinas. Raising the question of what is the meaning of escaping from this anonymity, the author shows that it is already the presumption or the influence of the intersubjective relation, and therefore also of ethics (which is inseparable from the intersubjective relation). Examining the Levinasian notion of existence also helps to reveal his criticism of Western philosophy, especially that of Martin Heidegger. The author claims that the separation of the existent from anonymous existence is not simply a reversal or even a modification of the Heideggerian ontological difference, but rather the first step towards an alterity that is not an ontological difference.